Normally off AlGaN/GaN HEMT on Si substrate with selectively dry-etched recessed gate and polarization-charge-compensation δ-doped GaN cap layer. (20th January 2015) - Wakejima, Akio; Ando, Akihiro; Watanabe, Arata; Inoue, Keita; Kubo, Toshiharu; Osada, Yamato; Kamimura, Ryuichiro; Egawa, Takashi
Abstract: We demonstrate a recessed-gate normally off AlGaN/GaN high-electron-mobility transistor (HEMT) on a silicon substrate that provides a precisely controllable threshold voltage ( V th ). To ensure V th uniformity, dry-etching of GaN with high etching selectivity between GaN and AlGaN is developed. Furthermore, to introduce selective dry-etching in the HEMT fabrication process, we propose a delta-doped GaN cap structure that enables negative polarization charges between the GaN cap and the AlGaN barrier to be compensated. Combining these two technologies, we fabricate recessed-gate normally off metal–insulator–semiconductor HEMTs with a subthreshold slope of 130 mV/dec and an on–off drain current ratio exceeding 10 7 .